Influencing factors of Chinese female college students sports participation: a case study - TANG YAO (Forest Chemicals Review)
The physical quality of adolescents is related to the future of the country and the nation. A healthy body cannot be separated from long-term physical exercise. Chinese government has begun to pay attention to the phenomenon of poor physical fitness and lack of physical exercise among young people, then has begun to strengthen the construction of school sports. However, The sports participation rate of Chinese college students is still not high, especially the sports participation rate of girls is much lower than that of boys. This study hopes to understand the factors that affect Chinese female college students sports participation. For this reason, the researchers conducted this study by observing and interviewing female college students who avoided exercise. The results showed that the sports participation behavior of female college students is not only based on their willingness to participate in sports, but also The school’s sports environment plays a positive role in promoting female college students sports participation.